Respect Without Recognition: A Critique of the OCSTA’s “Respecting Difference” Policy - Bialystok, Lauren (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
In 2012, a provincial bill amended the Ontario Education Act to provide more focused measures to eliminate bullying on the basis of sexual orientation. Bill 13 specifically requires that students be allowed to establish gay-straight alliances (GSAs), including in the publicly-funded Catholic school system. The Ontario Catholic School Trustees’ Association responded by proposing an alternative policy, called “Respecting Difference,” on the grounds that GSAs run contrary to Catholic teaching. Respect is a complex ethical notion with a long philosophical history. Through an overview of what philosophers from different traditions (including Kant, Buber, Levinas, Hegel, and Rawls) have said about respect, it becomes apparent that the kind of respect that is due to all persons requires recognition, or a willingness to accept the other as a self-identifying subject who is irreducible to my experience. In its discussion of LGBT students, the OCSTA fails to accord them such recognition, even while it emphasizes the meaning of difference. Consequently, there is reason to conclude that it does not truly respect sexual minority students and that it is not fully committed to eradicating homophobia-based bullying in the Catholic school system. “Respecting Difference” declines to heed best evidence about the factors that actually protect LGBT students from bullying, and uses the guidelines for “Respecting Difference” groups as an opportunity to reinforce its pathologization of LGBT identity itself.